2012
DOI: 10.1177/2156587212453050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serum Vitamin D Levels on Cardiovascular Mortality and Cardiovascular Disease Risk

Abstract: Vitamin D deficiency is prevalent across all geographic areas, age groups, and seasons and is increasing in incidence. Vitamin D receptors have been found to be present in almost every body cell and tissue. Clinical research has alluded to a preventive effect of vitamin D supplementation on cardiovascular disorders such as myocardial infarction, hypertension, and dyslipidemia. Furthermore, a low serum vitamin D level has been associated with an increased risk for cardiovascular disease. This article examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The prevalence of CHD in Australia has been reported to be 3.0% (males 4.4%, females 2.3%) [ 37 ] and the mean 10-year Framingham cardiovascular risk to be 6.3% [ 38 ]. Observational studies have suggested an association exists between vitamin D status and cardiovascular disease outcomes [ 39 ]. A meta-analysis in 2012 found a linear inverse association between vitamin D (ranging from 20–60 nmol/L) and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CHD in Australia has been reported to be 3.0% (males 4.4%, females 2.3%) [ 37 ] and the mean 10-year Framingham cardiovascular risk to be 6.3% [ 38 ]. Observational studies have suggested an association exists between vitamin D status and cardiovascular disease outcomes [ 39 ]. A meta-analysis in 2012 found a linear inverse association between vitamin D (ranging from 20–60 nmol/L) and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%